Śrī Gauḍīya gīti-guccha: an unprecedented collection of Sanskrit, Bengali, and Hindi devotional poems, prayers, and songs written by the Gauḍīya Vaiṣṇava Ācāryas - Bhaktivedānta Nārāyaṇa (Gauḍīya giti-guccha, 1999)
Vaishnava prayers with English translation.
Includes index.
Vaishnava prayers with English translation.
English, Bengali, and Sanskrit(Bengali and Sanskrit in roman).
Keywords: Vaishnavism / Prayers and devotions / Sanskrit.; Vaishnavism / Prayers and devotions / Bengali.; Vaishnavism / Prayers and devotions / English.